Manifestation and mitigation of node misbehaviour in adhoc networks - Khan, Burhan ul Islam; Olanrewaju, Rashidah Funke; Anwar, Farhat; Shah, Asadullah (Kaerntner Botanikzentrum, Klagenfurt, Austria, 2014)
Mobile adhoc network is signified as a boon for advance and future wireless communication system. Owing to its self-establishing network features and decentralization, the system can actually establish a wireless communication with vast range of connectivity with the other nodes. However, the system of MANET is also beheld with various technical impediments owing to its inherent dynamic topologies. Although there are abundant volume of research work, but very few have been able to effectively address the node misbehavior problems in MANET. The paper initially tries to draw a line between different types of nodes in MANETs based on their behavior characteristics, then reviews some of the significant contribution of the prior researches for addressing node misbehavior issues. A major emphasis is laid on is the researches which use game theory as a tool to study and address the misbehavior problems. The manuscript is developed considering some of the latest and standard evidences of past 5 years and finally discusses the open issues related to the problems.